2008
DOI: 10.1007/s11999-008-0397-y
|View full text |Cite
|
Sign up to set email alerts
|

Global Relevance of Literature on Trauma

Abstract: The trauma pandemic disproportionately kills and maims citizens of low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This imbalance in publications is most pronounced in Sub-Saharan Africa, which accounted for only 6% of the publications from developing countries. The paucity of publications emanating from the developing world highlighted in this study parallels the observations of others who have noted, in high-impact English-language orthopaedic journals, a paucity of studies dealing with the global trauma burden [23,24]. Similar findings were noted in a study detailing the representation of articles from the developing world in high-impact surgical journals [15].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This imbalance in publications is most pronounced in Sub-Saharan Africa, which accounted for only 6% of the publications from developing countries. The paucity of publications emanating from the developing world highlighted in this study parallels the observations of others who have noted, in high-impact English-language orthopaedic journals, a paucity of studies dealing with the global trauma burden [23,24]. Similar findings were noted in a study detailing the representation of articles from the developing world in high-impact surgical journals [15].…”
Section: Discussionsupporting
confidence: 88%
“…Publication of research from regions where the burden of disease is greatest is essential to furthering our understanding of the rising global burden of musculoskeletal conditions [1,2]. Clinical research conducted in developing countries has the added potential of providing evidence that can drive overall health policies [8,17,22,23,25]. The benefits of performing clinical research in the developing world and disseminating the results have been reported [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This skewed resource allocation is particularly pronounced in the orthopaedic literature where increased global musculoskeletal disease and trauma in the developing world have not been met with a concomitant increase in attention or funding [2,17,30]. Research is a way to contribute lasting change in a lowresource setting and is as important as research performed in a high-resource setting.…”
Section: Introductionmentioning
confidence: 99%
“…The SIGN organization, its implants, and the many surgeons in low and middle-income countries now using their techniques and equipment have effectively and dramatically changed the treatment paradigm for long-bone fractures and serve as an example of successful disruptive innovation [6]. In the developing world where resources are limited, traditional clinical research using standard followup and clinical outcomes is extraordinarily difficult, if not impossible, and research in these countries is severely underrepresented in the literature [9]. Although logistically challenging, it is worth critically examining the outcomes of the SIGN nail thus far.…”
Section: Introductionmentioning
confidence: 99%